Massive Popularity or Machine Politics: Which will Make the Next Philippine President? - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 7 No 4 (1992), 2009)
Forum held on April 30, 1992.